2014 5th International Renewable Energy Congress (IREC) 2014
DOI: 10.1109/irec.2014.6827021
|View full text |Cite
|
Sign up to set email alerts
|

Defect detection in thin-film photovoltaics; Towards improved efficiency and longevity

Abstract: Abstract-The Photovoltaic (PV) industry is seeking to increase efficiency and functional lifetime of PV modules manufactured on polymer substrates. High resolution and high speed surface inspection for the quality control of the manufacture of large area flexible PV modules are necessary to guarantee maximum quality, longer lifetime and enhanced product yield. Flexible PV films are the newest development in the renewable energy field and the latest films have efficiencies at or beyond the level of Si-based rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Water is a particularly common solvent in the synthesis process, biosensor, and the electrode of light-emitting and solar cells for Si QDs. Many recent experimental studies have shown that water-induced field effect, which caused the change of electrical conductivity of hydrogen-terminated silicon substrates. Furthermore, the photoluminescence (PL) spectra of silicon surface affected by water vapor can be used as a humidity sensor, , and Si QDs used as the electrode in light-emitting or solar cells are susceptible to degradation by water vapor. , Therefore, a critical fundamental question for Si QDs is whether and how the electronic structure and hence the PL properties is altered on the nanoscale, in particular, with the presence of water.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Water is a particularly common solvent in the synthesis process, biosensor, and the electrode of light-emitting and solar cells for Si QDs. Many recent experimental studies have shown that water-induced field effect, which caused the change of electrical conductivity of hydrogen-terminated silicon substrates. Furthermore, the photoluminescence (PL) spectra of silicon surface affected by water vapor can be used as a humidity sensor, , and Si QDs used as the electrode in light-emitting or solar cells are susceptible to degradation by water vapor. , Therefore, a critical fundamental question for Si QDs is whether and how the electronic structure and hence the PL properties is altered on the nanoscale, in particular, with the presence of water.…”
mentioning
confidence: 99%
“…15−18 Furthermore, the photoluminescence (PL) spectra of silicon surface affected by water vapor can be used as a humidity sensor, 19,20 and Si QDs used as the electrode in light-emitting or solar cells are susceptible to degradation by water vapor. 21,22 Therefore, a critical fundamental question for Si QDs is whether and how the electronic structure and hence the PL properties is altered on the nanoscale, in particular, with the presence of water.…”
mentioning
confidence: 99%
“…ELI is an imaging method to record images of radiation emitted from a photovoltaic cell that is powered in the forward direction [22]. The range of cell radiation measured, depending on the detector used, is 300-1250 nm [23][24][25][26]. The recommended exposure time ranges from 120 s [25] to 300 s [24] or 400 s [27].…”
Section: Electroluminescence Imaging (Eli)mentioning
confidence: 99%
“…The range of cell radiation measured, depending on the detector used, is 300-1250 nm [23][24][25][26]. The recommended exposure time ranges from 120 s [25] to 300 s [24] or 400 s [27]. This method allows characterization of individual photovoltaic modules/cells, as well as whole panels [8,23,28,29].…”
Section: Electroluminescence Imaging (Eli)mentioning
confidence: 99%
“…To realize highperformance hermetic packages, high-barrier films [1][2] and encapsulants [3][4] have been widely developed, and their moisture barrier properties must be studied. For this purpose, a reliable method of measuring water vapor transmission rates (WVTRs) under high-temperature conditions of 60 ˚C and 85 ˚C, such as those utilized for damp heat testing, [5][6] is required [7].…”
Section: Introductionmentioning
confidence: 99%